The Role of Digital Da'wah in Promoting Critical Consciousness and Democratic Values: A Socio-Religious Study in Indonesia - Dedi Muliadi; Syaibatul Aslamiyah; Mega Mesra Resmi; Murodi Murodi; Siti Uswatun Khasanah; Attabik Luthfi (Universitas Nurul Jadid, 2025)
In Indonesia's increasingly digital religious landscape, online da'wah has become a key agent in influencing public reasoning and civic engagement. This research aims to provide digital da'wah with the potential to be a transformational force in shaping a more critical, open, and active Muslim society in democratic socio-political life. Using a quantitative approach, as many as 100 respondents were randomly selected to fill out a validated questionnaire. The results of statistical analysis showed a significant positive relationship between digital da'wah and the formation of critical and democratic thinking, with a correlation coefficient value of r = 0.602 (p < 0.01). Simple linear regression analysis showed that digital da'wah significantly predicted the formation of critical and democratic thinking, with a regression coefficient value of β = 0.547 and a significance of p = 0.000 (p < 0.05). The R² value of 0.363 indicates that 36.3% of the variation in critical thinking and democratic attitudes can be explained by the digital da'wah variable. These findings confirm that digital da'wah not only plays a role as a medium for the dissemination of religious values, but also as a means of forming critical thinking awareness and involvement in the democratic process in Indonesian society.